Technical Notes and Result of Stereotactic Evacuation of Hematoma in Spontaneous Supratentorial Intracerebral Hematoma - Shrestha, Resha; Shrestha, Pranaya; Rajbhandari, Pravesh; Acharya, Samir; Dhakal, Sudan; Limbu, Chandra Prakash; Chandra, Avinash; Pant, Basant (Nepal Journal of Neuroscience, 2018)
Primary intracerebral hematoma constitutes about 10-15% of all strokes and is associated with high mortality and severe disability. Surgical treatment of intracerebral hemorrhage is quite controversial. It is believed that minimal invasive stereotactic surgery may reduce hematoma volume and decrease secondary neurotoxicity. The technical note of stereotactic surgery has been illustrated. A retrospective study from March 2016 to March 2018 has been conducted and all patients who underwent stereotactic evacuation of hematoma were included in this study. Baseline characteristics of patients and outcome in terms of Glasgow Coma Scale (GCS) and Modified Rankin Scale (mRS) have been shown. We have found significant improvement in GCS postoperatively, however mRS did not improve immediately but was significantly better in three months follow up period.